INFEKSI Human papillomavirus (HPV) 16/18 DAN KEJADIAN MUTASI p53 EKSON 8 PADA KANKER KEPALA DAN LEHER - , SITI HAMIDATUL 'A, Dr. biol. hom. Nastiti Wijayanti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Data from the World Health Organization (WHO) published in 2008 report that more than 7.6 million people worldwide die from cancer, 70% of occurred in developing countries and only 30% were successfully treated. In Indonesia cancers of the head and neck cancer dari.insidensi ranked fourth nationally. Head and neck cancer incidence in relation to several factors, including, smoking, alcohol, viral infection human papillomavirus (HPV) and genetic factors. Mutations in the p53 gene result in changes in protein structure TP53 and related to the incidence of cancer, particularly cancers of the head and neck. HPV E6 oncoprotein binds and inactivates TP53, and result in loss of cell cycle control. This study aimed to detect the presence of HPV infection genotypes 16 and 18, detecting p53 mutations in exon 8, and observe the relationship between infection with HPV 16/18 with p53 mutations in exon 8. Observations genotypes of HPV and p53 mutations performed on three types of samples (Formalin Fixed Paraffin Embedded (FFPE), fresh tumor tissue and peripheral blood) to determine the most appropriate type of biosampel for this study. Further sequencing of p53 exon 8 performed on samples derived from 4 subjects who had all three types biosampel. A total of 33% (11/33) FFPE samples and 14% (2/14) fresh tissue samples were positive for HPV 18 infection (single DNA band size 415bp) and no detectable infection with HPV 16. Amplification of DNA was observed in p53 exon 8 all samples (absence of DNA band size 194 bp). Furthermore, sequencing of p53 exon 8 showed a heterozygot point mutation in the FFPE samples (L10F) where the base C / G mutated into a T / A. Mutations that occur at codon 282 not cause TP53 conformation change. In this study could not be concluded biosampel type most suitable for studies related to HPV infection and p53 mutation in exon 8 of head and neck cancer. Furthermore, the testing needs to be done on samples with larger amounts to so as to represent the prevalence of oncogenic HPV infection in Indonesia, and its relation to p53 mutations as a whole.